Pengaruh Rasio Pasar, Rasio Solvabilitas dan Makro Ekonomi terhadap Harga Saham pada PT Ultrajaya Milk Industry Tbk Periode 2013-2022 - Prasetyo, Muhamad Asraf; Octovian, Reza (Jurnal Disrupsi Bisnis, 2024)
This research aims to find out whether there is an influence between Market Ratio (EPS), Ratio Solvency (DER), and Macroeconomics (Inflation) on share prices for the 2013-2022 period. The method used in this research is quantitative descriptive using financial reports from PT Ultrajaya Milk Industry & Trading Company Tbk for the 2013-2022 period, which are listed on the Indonesia Stock Exchange, and inflation data from the Bank Indonesia website. The data analysis used is descriptive statistical tests, classical assumption tests, regression analysis, hypothesis testing, and coefficient of determination analysis using software SPSS version 25. The results of this study show that partial Earning Per Share has a significant effect on share prices, Debt To Equity Ratio has no significant impact on stock prices and inflation has a significant effect on stock prices. Meanwhile, simultaneously Earning Per Share, Debt To Equity Ratio, and Inflation together have a significant effect on stock prices. Based on the coefficient of determination test, the results show 0.893 or a percentage of 89.3%. This shows that the variable Earning Per Share, Debt To Equity Ratio, and Inflation of 89.3%, which means that the level of these three ratios is strong on share prices, and around 10.7% is influenced by other variables not examined in this research.